Pendidikan Multikultural dalam Pembelajaran Sejarah di SMA Negeri 1 Sitiung - Nisa Ulaini; Yera Zettira Agesti (Tarikhuna: Journal of History and History Education, 2022)
This article is entitled "Multicultural Education in History Learning at SMA Negeri 1 Sitiung". The writing of this article is motivated by the ethnic diversity that exists in the SMA Negeri 1 Sitiung environment. In this school there is a fairly complex diversity such as ethnic, cultural, racial, and religious diversity. Usually this is one of the factors that causes conflict in the community but not with the diversity that exists in SMA Negeri 1 Sitiung, with differences, the atmosphere and social conditions of students in it remain peaceful and avoid conflict. The aims of this study are: (1) To find out the historical background of the occurrence of multiculturalism in SMA Negeri 1 Sitiung. (2) Knowing the implementation of multicultural education in history learning at SMA Negeri 1 Sitiung. This type of research is case study research, using descriptive qualitative research methods. Research informants were Indonesian History teachers, students and principals and vice principals for student affairs. Data collection techniques used are observation, interviews and documentation. Based on the results of the study, it can be obtained data that multicultural education has been applied in history learning by history teachers at SMA Negeri 1 Sitiung. Multicultural values are incorporated into the history subject matter, so that a combination occurs in the history learning process. Multicultural education at SMA Negeri 1 Sitiung is not only implemented in classroom learning, but is also included in the agendas of activities and habits at school. So as to create a comfortable, peaceful, and peaceful atmosphere in the SMA Negeri 1 Sitiung environment. Keywords: Education, Multicultural, History Learning.